OVERCOMING STUDENTS’ PROBLEMS IN PRONOUNCING PAST TENSE VERBS BY MEANS OF YOUTUBE VIDEO - Junjun Ahmad Santosa (Universitas Galuh, 2021)
This study was aimed to discover whether teaching by using Youtube videos could overcome students’ problem in pronuncing past tense verbs and to discover the students’ perceptions on the use of Youtube video as teaching media. This study mixed-method study involved the eight grade students of junior high school in Ciamis Year 2017/2018 at which the sample was 27 students of experimental group and 27 for control group. Pre-test and post-test were employed to collect the quantitative data and close-ended questionnaires to collect the qualitative data. The findings indicated that t-observed was 2.344 with degree of freedom 52 and level of significance 0.05 with two tailed test t-table (2.021). It implied that t-observed was higher than t-table (2.344 > 2.021) resulting in rejecting Null hypothesis. It means that there were significant differences on the students’ pronunciation achievement who were taught before using YouTube video and after using YouTube video. Also, students have positive perceptions toward the use of Youtube video as teaching media to overcome their problem in pronouncing past tense verbs such as feeling more intellegent, interested and effective in learning speaking especially pronunciation. This study suggested that Youtube video as media can be applied in other level of students. Keywords: Pronunciation, Past Tense, Youtube Videos